The Association between Physical Activity, Dietary Behavior and Body Mass Index among Saudi Women Living in KSA and UK - Al-Hajri, Ahlam Saleh; McCullough, Fiona; Salter, Andy (Journal of medical and pharmaceutical sciences, 2019)
This study investigates the association between Physical Activity (PA) and dietary intake with Body Mass Index (BMI) among Saudi women living in Saudi Arabia and women living in the UK. A survey of a snowball sample was used to recruit 258 female and explored factors influencing PA and food intake and their effects on BMI in women living in KSA and UK. Participants completed a self-reporting questionnaire relating to knowledge, attitudes, barriers, and levels of PA, sedentary activity and eating habits. Several results were concluded, most importantly: 1) Excessive energy intake, physical inactivity, and sedentary lifestyle were all prevalent in Saudi women, resulting in 80%, over the age of 35 years being overweight or obese. 2) BMI was associated with both energy intake and PA, though the relationship with the former was stronger. The most common barriers to regular exercise were transportation and lack of time. 3) Findings were generally similar between women living in Saudi Arabia and the UK. 4) This study confirms that excessive dietary intake and physical inactivity both contribute to overweight and obesity in Saudi Arabian women.